Protection of Rhesus Macaques against Lethal Plasmodium knowlesi Malaria by a Heterologous DNA Priming and Poxvirus Boosting Immunization Regimen - Rogers, William O. (American Society for Microbiology, 2002)
We tested a cytokine-enhanced, multiantigen, DNA priming and poxvirus boosting vaccine regimen for prevention of malaria in the Plasmodium knowlesi-rhesus macaque model system. Animals were primed with a mixture of DNA plasmids encoding two preerythrocytic-stage proteins and two erythrocytic-stage proteins from P. knowlesi and combinations of the cytokines granulocyte-macrophage colony-stimulating factor, interleukin-4, and tumor necrosis factor alpha and were boosted with a mixture of four recombinant, attenuated vaccinia virus strains encoding the four P. knowlesi antigens. Two weeks after boosting, the geometric mean immunofluorescence titers in the immunized groups against sporozoites and infected erythrocytes ranged from 160 to 8,096 and from 1,810 to 5,120, respectively. The geometric mean anti-P. knowlesi circumsporozoite protein (PkCSP) titers ranged from 1,761 to 24,242. Peripheral blood mononuclear cells (PBMC) from the immunized monkeys produced gamma interferon (IFN-γ) in response to incubation with pooled peptides from the PkCSP at frequencies of 10 to 571 spot-forming cells/10(6) PBMC. Following challenge with 100 infectious P. knowlesi sporozoites, 2 of 11 immunized monkeys were sterilely protected, and 7 of the 9 infected monkeys resolved their parasitemias spontaneously. In contrast, all four controls became infected and required treatment for overwhelming parasitemia. Early protection was strongly associated with IFN-γ responses against a pool of peptides from the preerythrocytic-stage antigen, PkCSP. These findings demonstrate that a multistage, multiantigen, DNA priming and poxvirus boosting vaccine regimen can protect nonhuman primates from an otherwise lethal malaria sporozoite challenge.